Choices & change : macroeconomics. - Harrison, Ken; Harrison, Ken; Owens, Katherine (Academic Video Online, 2000)
This Part 3 of 9 of the Lesson 3, Supply & Demand is about The Law of Demand, wherein the lower the price, the greater the quantity demanded.